ISSUES OF INNOVATION MANAGEMENT AND PRACTICAL IMPLEMENTATION IN ENTERPRISES. - Dadajonova Martakhon Maҳmudovna,,; Mannobov Alijon Sharifjonovich, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
This article discusses the key challenges in the innovation management process by identifying the key factors that determine the competitive advantage of an enterprise.